Construction of LSPR-enhanced 0D/2D CdS/MoO3−x S-scheme heterojunctions for visible-light-driven photocatalytic H2 evolution - Peng, Jinjun; Shen, Jun; Yu, Xiaohui; Tang, Hua; Zulfiqar; Liu, Qinqin (Chinese journal of catalysis, 2021)
Plasmonic nonmetal semiconductors with localized surface plasmon resonance (LSPR) effects possess extended light-response ranges and can act as highly efficient H2 generation photocatalysts. Herein, an LSPR-enhanced 0D/2D CdS/MoO3−x heterojunction has been synthesized by the growth of 0D CdS nanoparticles on 2D plasmonic MoO3−x elliptical nanosheets via a simple coprecipitation method. Taking advantage of the LSPR effect of the MoO3−x elliptical nanosheets, the light absorption of the CdS/MoO3−x heterojunction was extended from 600 nm to the near-infrared region (1400 nm). Furthermore, the introduction of 2D plasmonic MoO3−x elliptical nanosheets not only provided a platform for the growth of CdS nanoparticles, but also contributed to the construction of an LSPR-enhanced S-scheme structure due to the interface between the MoO3−x and CdS, accelerating the separation of light-induced electrons and holes. Therefore, the CdS/MoO3−x heterojunction exhibited higher photocatalytic H2 generation activity than pristine CdS under visible light irradiation, including under 420, 450, 550, and 650 nm monochromic light, as well as improved photo-corrosion performance. The MoO3-x/CdS heterojunctions exhibit improved photocatalytic H2 generation activity, which is accredited to an LSPR-enhanced S-scheme charge transfer mechanism.